Nikah Misyar Perspective Of Women And Child Protection Law - Mariani, Mariani (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
Marriage in Islam is conceived as a mitsaqan ghalizha (a solemn covenant) intended to establish a harmonious family characterized by sakinah (tranquility), mawaddah (love), and rahmah (compassion). However, contemporary social dynamics have introduced alternative marriage practices, one of which is Nikah Misyar. In this arrangement, typically the wife voluntarily waives certain rights such as financial maintenance, housing, or a turn in polygamy. While often motivated by professional obligations, geographical separation, or social considerations, this practice has raised concerns for its potential to undermine women’s and children’s rights as well as broader moral and social values. This study adopts a qualitative method with a normative and descriptive-analytical approach to examine Nikah Misyar from the perspective of Indonesian law on the protection of women and children, alongside its social and psychological implications. The findings reveal that although Nikah Misyar may be valid under Islamic law if the essential pillars and conditions are met and properly registered, it risks contravening legal principles of protection. In particular, women’s and children’s rights to maintenance and custody are highly vulnerable, as the voluntary waiver of such rights lacks a strong legal mechanism for future enforcement.